Enhancing Learning Outcomes on Monetary and Fiscal Policy through a Flipbook E-Module with a Problem-Based Learning Approach - Rukia Kumala Sari Siregar; Abdul Hasan Saragih; Saidun Hutasuhut (FINGER : Jurnal Ilmiah Teknologi Pendidikan, 2025)
Background: Learning outcomes in economics particularly in topics such as monetary and fiscal policy often remain suboptimal among high school students due to the abstract nature of the content and the limited use of engaging instructional media. Traditional teaching methods that rely heavily on printed textbooks tend to reduce student interaction and hinder the development of independent learning skills.Aims: This study aimed to develop and evaluate a flipbook-based e-module integrated with the Problem-Based Learning (PBL) model to enhance students’ conceptual understanding and academic achievement in economics.Methods: Using the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation), the e-module was designed and validated by experts in content, media, and instructional design. The validation was followed by individual, small-group, and field testing. The module’s effectiveness was assessed using a quasi-experimental design that compared pre-test and post-test scores between experimental and control groups. Data were analyzed using descriptive statistics, inferential statistics, and N-Gain calculations.Result: The e-module received high validity ratings: 89.3% from subject matter experts, 85.43% from media experts, and 88.3% from instructional design experts. Practicality ratings were also high, with 95.53% from teachers and 90.40% from students. The experimental group showed significantly higher post-test scores (M = 80.00) than the control group (M = 63.56), with a medium N-Gain score of 0.5192, indicating an improvement in learning.Conclusion: The flipbook-based e-module integrated with the Problem-Based Learning approach is a valid, practical, and effective learning tool. It promotes student engagement, supports independent learning, and significantly improves academic performance in economics education.